When corporate actors take over the game: the corporatization of organic, recycling and breast cancer activism. (3rd September 2017) - King, Leslie; Busa, Julianne
Abstract: Social change endeavors are increasingly shaped by corporate interests and, in some instances, large corporations take over ideas and practices initiated by social change advocates. We label this process 'corporatization' and argue that, while it is clearly a variant of co-optation, it has specific qualities that warrant a separate analytical framework. Using existing research to examine the cases of breast cancer activism, organic food, and recycling in the United States – all extreme examples of corporatization – we conceptualize corporatization as a subset of co-optation in which: (1) corporations come to dominate fields initiated by activists; (2) corporatized versions become widespread; and (3) alternative, 'response, ' movements emerge to oppose corporatized versions. We posit that, in each case, 'corporate takeover devices' allowed corporate entities to 'join the game' and eventually come to dominate fields initiated by social movements.